Tanggung Jawab Orang Tua Kepada Anak di Era Digital Perspektif Hukum Keluarga Islam di Indonesia - Yasin, Nur Ahmad (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2018)
The digital age is an era where technology and information can be accessed by anyone, anywhere and under any conditions, so that it can have a positive and negative impact on parents’ responsibilities to children and child development. This article is the result of a bibliographical study on parents’ responsibilities to children in the digital age under the perspective of Islamic family law in Indonesia. Data are collected using documentation techniques and analyzed using descriptive methods with deductive mindset. Based on this study, parents are responsible for being more selective in nurturing, educating, and protecting children in today’s digital era. They are also asked to understand information technology and systems. Parents must be able to actualize children’s rights, including: maintenance of honor (ḥifẓ al-'irḑ), maintenance of religious rights (ḥifẓ al-dīn), maintenance of the soul (ḥifẓ al-nafs), maintenance of reason (ḥifẓ al -'aql) and maintenance of property (ḥifẓ al-māl). [Era digital merupakan era di mana teknologi dan informasi dapat diakses oleh siapapun, dimanapun dan dalam kondisi apapun, sehingga dapat berdampak positif dan negatif terhadap tanggung jawab orang tua kepada anak dan perkembangan anak. Artikel ini merupakan hasil penelitian pustaka tentang tanggung jawab orang tua kepada anak di era digital perspektif hukum keluarga Islam di Indonesia. Data dihimpun dengan menggunakan teknik dokumentasi dan dianalisis menggunakan metode deskriptif dengan pola pikir deduktif. Berdasarkan penelitian ini, orang tua bertanggung jawab untuk lebih selektif dalam mengasuh, memelihara, mendidik, dan melindungi anak di era digital saat ini. Mereka juga ditutut memahami teknologi dan sistem informasi. Orang tua harus dapat mengaktualisasikan hak-hak anak, diantaranya: pemeliharaan atas kehormatan (ḥifẓ al-‘irḑ), pemeliharaan atas hak beragama (ḥifẓ al-dīn), pemeliharaan atas jiwa (ḥifẓ al-nafs), pemeliharaan atas akal (ḥifẓ al-‘aql) dan pemeliharaan atas harta (ḥifẓ al-māl).]